Boy Scout meeting room - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a Boy Scout meeting room. The room is filled with flags and certificates. Various types of knots are on display. A board in the doorway reads "Troop 22 Boy Scouts of America. Scout Hall." A ribbon posted on the wall reads: "Hike-o-ree, 1944."